ADJECTIVE CHECK LIST PENGUNGKAP STEREOTIP LAKI-LAKI DAN PEREMPUAN MENURUT PERSEPSI MAHASISWA DARI SEPULUH ETNIS - Wening Sahayu (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2011)
This study aims to describe male and female stereotypes based on the perceptions of students from ten ethnic groups in Indonesia and agreed upon by all of them and to compare such stereotypes with the research findings by Best and William. The respondents were students from ten ethnic groups, i.e. Jawa, Papua,Sunda, Bali, Madura, Lombok, Batak, Minangkabau, Aceh, dan Betawi. The survey employed a questionnaire with fifty adjectives representing characters referring to the study by Best and William. The data were descriptively analyzed using tabulation and percentage. The findings are as follows. First, students from each ethnic group have a variety of perceptions regarding male and female stereotypes agreed upon. Second, there are a number of male and female stereotypes agreed upon by students from all ethnic groups. Third, the male stereotypes relevant to the study by Best and Williams are strength, dominance, autonomy, and aggression. The female stereotypes relevant to both studies are passiveness, weakness, and abasement.